Implementation of Network Security and Anticipating Attackers Using pfSense Firewall - Alhu Waladan Naufal Sholihan; Aan Restu Mukti; Suryayusra Suryayusra; Rahmat Novrianda Dasmen (CESS (Journal of Computer Engineering, System and Science), 2023)
At PT. PLN (Persero) UPDL Palembang uses routers from the Cisco 1900 series, hardware-wise this Cisco device is very old because it was released in 2009 according to a Cisco website source, using the Cisco 1900 series as a router is something that is very vulnerable to attack by attackers due to its backwardness. the times in terms of network security, and the lack of attention to network security is also a matter of concern in this regard. With these problems, routing is added for network security by designing a pc router firewall from pfSense, the pc router itself uses computer assets that are is no longer used but has sufficient specifications. Using the action research method, carrying out diagnoses, planning actions, following up, conducting evaluations, and learning materials. By designing a pc router firewall using pfSense it is hoped that the results will be quite good, because it uses the router firewall feature using pfSense to block attacks. Using pfSense as network security will certainly be safer because pfSense still regularly updates or improves its security and has an active forum community to date so that information can be exchanged.